Architectural graphic standards - Bassler, Bruce L (Wiley, 2008)
Student edition is an abridgment of the 11th ed.; Includes bibliographical references and index; KR014 Vật lý kiến trúc 01: Quang học; KR037 Vật lý kiến trúc 02: Nhiệt - Khí hậu; KR069 Chuyên đề kiến trúc 03: Trang thiết bị công trình